Seismic stratigraphy study of the east Razzaza within late Jurassic –early Cretaceous era (Central Iraq) - Khorshid , Salman Z.; AL-Sharaa , Ghazi H.; Ali, Layalen H. (Iraqi Journal of Science, 2022)
This study deals with seismic structural and stratigraphic interpretation that applied on the East Razzaza (central of Iraq) area, by using 2D seismic data from Oil Exploration Company. Three main seismic reflectors are picked. These reflectors are Zubair, Yamama and Gotnia Formations, which were defined by using petrophysical well logs and synthetic traces that calculated from sonic- logs of the wells East Baghdad-1(Eb-1) and West kifl-1(Wk-1) using Geoframe program, to suggest a stratigraphic model for them. Structural maps of formations are prepared to obtain the location and direction of the sedimentary basin and shoreline. Seismic interpretation of the area approves the presence of some stratigraphic features in the studied formations. Some distributary buildup mound and carbonate platform. Yamama is interpreted here to represent a carbonate platform. Seismic attributes technique was used to predict the physical properties distribution of Yamama succession. Instantaneous frequency and amplitude maps of Yamama shows low anomaly, this may indicate porous calcareous rocks in that location that contain fluids.